Height Measurement With Meter Wave MIMO Radar Based on Precise Signal Model Under Complex Terrain - Song, Yuwei; Hu, Guoping; Zheng, Guimei (IEEE access, 2021)
Meter wave radar height measurement is one of the most difficult problems in meter wave radar system. At present, the most popular height measurement methods of meter wave radar include beam splitting method, MUSIC algorithm and maximum likelihood estimation method, which can achieve good performance under flat ground. However, the real ground is not ideal condition, and the situation of undulating ground is also very complicated. Under this condition, the performance of the above algorithm dropped sharply. Many researchers solve this problem by improving the robustness of the algorithm. However, the authors think that the key to solve the problem is to establish a refined height measurement signal model. In this paper, the accurate model of reflection coefficient, reflection height and reflection point under the condition of undulating ground are established to provide accurate signal model for meter wave radar height measurement. Then we deduce the application of generalized MUSIC algorithm and maximum likelihood estimation algorithm for MIMO radar in the accurate terrain signal model. In fact, the method proposed in this paper is a terrain matching MIMO radar target height measurement, and the traditional algorithm can be regarded as terrain mismatch. The simulation results show that the accuracy of terrain matching estimation of the precise signal model established in this paper is much better than that of the traditional simplified signal model.